Understanding chess endgames - Nunn, John
Assuming no specialized endgame knowledge, john Nunn presents 100 key endgame concepts, and shows how they are used to win games or save difficult positions. He describes the most important ideas in all the main types of endgames and so equips readers with all the skills needed to excel in this vital phase of the game up to good club level and beyond. The endgame is the stage of the game where precision is most important, and where errors are punished most drastically. It is also deceptive: many endgame positions look too simple to require prior knowledge, but contain concealed pitfalls that can lead to disaster. Knowing the key concepts and positions gives a tremendous advantage, especially when playing with today's faster time-controls. In perilous terrain, an expert guide is necessary. John Nunn could not be better qualified: he is battle-hardened grandmaster of top-level over-the-board chess, a solving world champion and has previously written several highly acclaimed works on the endgame. From his wealth of endgame expertise, he has distilled a course of fundamental knowledge that is tightly focused on practical success for all levels of players.